Ultralight graphene aerogel/PVDF composites for flexible piezoelectric nanogenerators. (December 2020) - Guo, Yiting; Xu, Jie; Wu, Wanli; Liu, Shuhang; Zhao, Jia; Pawlikowska, Emilia; Szafran, Mikołaj; Gao, Feng
Abstract: Graphene aerogel/PVDF (GA/PVDF) composites with a three-dimensional structure were prepared using a vacuum-assisted impregnation process. The phase structure, morphology and piezoelectric properties have been systematically studied. The results show that GA/PVDF composites have good piezoelectric output characteristics and can provide corresponding feedback according to the magnitude and frequency of the acting force. When the PVDF concentration is 80 mg/mL, the GA/PVDF composite reaches the highest piezoelectric constant ( d 33 = 16 pC/N). The average peak output current is approximately 0.51 μA and shows good stability under repeated pressing. It is promising to apply to the field of flexible pressure sensors that can be self-powered. Highlights: Graphene aerogel/PVDF composites with 3D structure were fabricated via vacuum-assisted impregnation process. The GA/PVDF composites show high porosity and good flexibility. The GA/PVDF composites have good piezoelectric output characteristics and can make corresponding feedback to the acting force. The GA/PVDF composites reached the highest d33 of 16 pC/N and an average peak output current of about 0.51 μA.